Representation and Governance in International Organizations - David P. Rapkin; Jonathan R. Strand; Michael W. Trevathan (Politics and Governance, 2016)
What does representation mean when applied to international organizations? While many scholars working on normative questions related to global governance often make use of the concept of representation, few have addressed specifics of applying the concept to the rules and practices by which IOs operate. This article examines representation as a fundamental, albeit often neglected, norm of governance which, if perceived to be deficient or unfair, can interfere with other components of governance, as well as with performance of an organization’s core tasks by undermining legitimacy. We argue that the concept of representation has been neglected in the ongoing debates about good governance and democratic deficits within IOs. We aim to correct this by drawing on insights from normative political theory considerations of representation. The article then applies theoretical aspects of representation to the governance of the International Monetary Fund. We determine that subjecting IOs to this kind of conceptual scrutiny highlights important deficiencies in representational practices in global politics. Finally, our conclusion argues scholars of global governance need to address the normative and empirical implications of conceptualizing representation at the supranational level.